THE INFLUENCE OF STUDENTS’ LEARNING STYLE TOWARDS STUDENTS’ MATHEMATICS KNOWLEDGE - Wigati Indah Sari; Heni Pujiastuti (IAIN Ambon, 2020)
The purpose of the research was to determine how far the influence of the ability of students’ mathematical understanding learning style. The subjects in this study were 140 11th grade students of SMK Bina Am-Mak'mur Tangerang Regency Year 2019/2020 which was classified into three learning style groups, which was visual learning style consisting of 32 students, auditorial consisting of 23 students, and kinesthetic consisting of 85 students. The method in this study was ex post facto to know clearly the data on students’ ability of mathematical understanding learning style. The data were taken and processed using the normality test and homogeneity test with Anava One Way, to determine the influence of students ' learning style more clearly. After the test, it can be concluded that the average value of the results of the mathematical understanding of students with visual learning style was better than the average value of the results of the mathematical understanding of students with auditory and kinesthetic learning styles.